Intercultural Communication Based on Local Wisdom That Made the People of Bali Reject Sharia Tourism - Dewi Sumiati (Asian Journal of Media and Communication, 2017)
Bali is one of the provinces in Indonesia which is very popular among domestic and foreign tourists. On December 2015, there was an idea of developing sharia tourism in Bali which has strong culture based on Hindu religion. The idea is being opposed by the Balinese people and it resulted in many negative response as the idea is contradicted with Regional Regulation of Bali regarding Culture Tourism. The formulation of the problem in this research is to find out how intercultural communication based on local wisdom that made the people of Bali reject sharia tourism. This study uses a case study with qualitative descriptive approach. Data collected by in-depth interview and observation as the primary data, while the study of literature, internet, and documentaries as secondary data. This study found that there is a positive intercultural communication between the Hindu and Muslim communities in Bali. The Muslim community who lived in Bali also rejected sharia tourism being developed in Bali. Based on these results, the author concluded that positive intercultural communication combine with strong tradition of local wisdom will form an integrated culture.Â Keywords: intercultural communication, local wisdom, sharia tourism, integrated culture